Translation, Cultural Adaptation and Validation of the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) in Italian - Battista Rosa Alessia; Ferraro Milena; Piccioni Lucia Oriella; Abdelwahab Mohamed; Battista Federica; John Michael; Saltychev Mikhail; Most Sam P.; Bussi Mario (Springer, 2025)
Backgrounds Rhinoplasty necessarily concerns functional and cosmetic aspects, and outcomes of both should be assessed in each patient. There has been a lack in the literature in Italian for a comprehensive tool for assessing both aspects of rhinoplasty. The objective is to translate and validate the Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) into Italian.
Methods Forward and back-translation was used. Content validity was evaluated by experts and by patient interviews. Internal consistency was assessed by a Cronbach's alpha. The structure validity was assessed by an exploratory factor analysis.
Results Cognitive interviews of 10 rhinoplasty patients resulted in a good overall comprehension of the SCHNOS. Of the 411 respondents, 281 (32%) were women, and the average age was 33.6 (11.3) years. The alpha was excellent for both the obstruction domain (SCHNOS-O) (0.90) and the cosmetic domain (SCHNOS-C) (0.94). All the correlations between repeated measures were moderate to very strong. The exploratory factor analysis demonstrated unidimensionality of both the SCHNOS-O and the SCHNOS-C scores.
Conclusions The SCHNOS was successfully translated and validated in Italian and can be recommended for a clinical use among rhinoplasty patients.